Two new species of Bryconamericus Eigenmann (Characiformes: Characidae) from southern Brazil - Silva,José Francisco Pezzi da (2004)
Two new species of Bryconamericus are described from southern Brazil: B. patriciae, from the headwaters of rio Pelotas (rio Uruguay drainage) and rio das Antas (laguna dos Patos drainage) and B. ecai from lower rio Taquari drainage. Bryconamericus patriciae differs from other Bryconamericus species from southern South America, by the following combination of characters: body depth (25.5-30.3% SL); head length (25.2-27.6% SL); pelvic-fin length (11.0-14.4% SL); branched anal-fin rays 14-18; teeth of outer row of premaxilla regularly implanted; teeth of inner row of premaxilla pentacuspid; teeth compressed distally; and males with bony hooks on pelvic and anal fins. Bryconamericus ecai differs from other Bryconamericus species from southern South America by the following combination of characters: body depth (33.1-36.9% SL); eye diameter (31.1-33.9% HL); snout length (26.8-32.4% HL); branched anal-fin rays 15-18; teeth of outer row of premaxilla regularly implanted; teeth of inner row of premaxilla tricuspid or pentacuspid; teeth compressed distally; and males with bony hooks on pelvic and anal fins.